Analisis Penurunan Jumlah Penerbangan an Penerapan Strategi Pemasaran Wings Air Dalam Masa Pandemi Covid – 19 Di Bandar Udara Douw Aturure Nabire Papua - Auly Utari; Elisabeth Endang Prakosawati (LPPM Institut Nasional Laa Roiba Bogor, 2022)
The impact of the Covid-19 pandemic has greatly affected all operating systems. One of the airlines from the Lion Air Group (Wings Air) decided to temporarily suspend flight operations after many of their prospective passengers canceled their flights due to travel document reasons. This study aims to determine the impact of the Covid-19 pandemic on the decline in the number of Wings Air flights and to find out the marketing strategies carried out by the Wings Air airline during the Covid 19 pandemic. This research uses qualitative methods with descriptive qualitative research. This study takes data on documentation, observations, and interviews conducted with the Wings Air Manager, Ground Handling Wings Air, and Wings Air Staff. The data analysis technique uses data organizing, data management, data verification and interpretation, and conclusion drawing. This research was conducted at Douwaturure Nabire Airport, Papua. The results of the research conducted by researchers, that the number of Wings air flights at Douwaturure Nabire Airport decreased by 90% from 4-5 flights per day to 1-2 flights per day. As for the marketing strategy carried out by Wings Air during the pandemic, the airline carried out a strategy by informing it through the Via wa Group, or using Traveloka and agents in nabire. Keywords : Number of Flights, Marketing Strategy, Douwaturure Nabire Airport